Interacting with the Past: Historical Sciences and Historical Games - David Černín (Teorie vědy)
Historical video games are uniquely tied to the scientific practices of professional historians, archaeologists, and many other experts. However, since video games are an interactive medium and the most common-sensical view of history is that the past is fixed, it is clear that, at least from a representationalist point of view, there is some unresolved tension. The article explores this predicament and draws heavily from contemporary historical non-representationalism – a position that shifts focus from the idea of representing the real past to the close examination of historical discourse as a complex argumentative practice, relying on evidence and robust theoretical background. To complement the theoretical examination of the problem, the paper examines three examples from historical discourse (the Late Bronze Age collapse, cliodynamics, and Big History) and juxtaposes them against two examples of historical video games of a strategic genre that deal with related topics. It is argued that what makes video games historical is their complex relation to the ongoing historical discourse.